2020
DOI: 10.1371/journal.pone.0243632
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, wound healing and antioxidant potential of compounds from Dioscorea bulbifera L. bulbils

Abstract: Background Dioscorea bulbifera L. (Dioscoreaceae) has been traditionally used in Thai folk medicine as a diuretic and anthelmintic, for longevity preparations, and for wound and inflammation treatment. This plant is also commonly used in traditional Indian and Chinese medicines in the treatment of sore throat, gastric cancer, rectal carcinoma and goiters. However, the wound healing effects of the active compounds in this plant have not been investigated. Objective This study aimed to identify compounds respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
(58 reference statements)
3
18
0
Order By: Relevance
“…The antioxidant activity of the D. bulbifera extract/honey-loaded Gan/XG after being incubated for 1 h significantly increased when the incubation time increased. The result of the D. bulbifera extract/honey-loaded Gan/XG correlated with a previous study showing that the ethanolic extract of D. bulbifera bulbils exhibited antioxidant activity by the DPPH radical scavenging assay [25]. The antioxidant patches are the alternative for treatment of difficult-to-heal wounds because the antioxidants help to manage wound oxidative stress and balance the level of reactive oxygen species [37][38][39].…”
Section: Samples Incubation Time (H) 1 H 2 H 4 H 6 Hsupporting
confidence: 85%
See 2 more Smart Citations
“…The antioxidant activity of the D. bulbifera extract/honey-loaded Gan/XG after being incubated for 1 h significantly increased when the incubation time increased. The result of the D. bulbifera extract/honey-loaded Gan/XG correlated with a previous study showing that the ethanolic extract of D. bulbifera bulbils exhibited antioxidant activity by the DPPH radical scavenging assay [25]. The antioxidant patches are the alternative for treatment of difficult-to-heal wounds because the antioxidants help to manage wound oxidative stress and balance the level of reactive oxygen species [37][38][39].…”
Section: Samples Incubation Time (H) 1 H 2 H 4 H 6 Hsupporting
confidence: 85%
“…Moreover, the viability of cells treated with the extraction media of the D. bulbifera extract/honey-loaded Gan/XG and the unloaded Gan/XG at the concentration of 1 mg/mL was significantly higher than the control (Figure 7). The results of the D. bulbifera extract/honey-loaded patch related to the previous study of D. bulbifera ethanolic extract with concentrations from 1 to 100 µg/mL that exhibited low toxicity [25].…”
Section: Nhf Cell Viabilitysupporting
confidence: 78%
See 1 more Smart Citation
“…Among the natural polyhydroxy flavonoids, quercetin has strong antioxidant and anti-inflammatory properties to regulate oxidative stress and inflammation, which delay the wound healing process [ 9 ]. It has been shown that quercetin can promote the wound healing process by modulating inflammatory cells and increasing fibroblast proliferation while decreasing immune cell infiltration, fibrosis and scar formation, and creating changes in signaling in fibrosis-associated signaling pathways [ 10 , 11 , 12 ]. A previous report revealed that quercetin accelerated diabetic wound repair by inhibiting inflammatory reactions via modulating macrophage polarization [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, colorimetric phytochemical test was used to confirm the presence of catechin and quercetin in PCFHE, indicating that the wound healing and antimicrobial effects of PCFHE are attributable to its phyto-components particularly catechin and quercetin. This assertion is in view of the confirmed wound healing, antioxidant, anti-inflammatory, and antimicrobial effects of catechin and quercetin [ 44 , 45 ]. For instance, quercetin and catechins demonstrate free radical scavenging, anti-inflammatory, antioxidant, antihistamine effect, inhibition of matrix metalloproteinase, and promote collagen synthesis [ 46 48 ], and all these properties are crucially involved in wound healing process [ 49 ].…”
Section: Discussionmentioning
confidence: 98%